(3ebGdI gQeS GdMcje aj GdCdhGfs - (3GdMcje gQeS , gQeS GdgQGeSIs
(3ChdgG (B:s
(3Gddhf LfS ef GdCLfS hEfeG LfS GdCLfGS dCfg jbSe GdShGO hGdHjGV s
(3BNQgG (B:s
(3hcPdc CjVkG fhQ GdTeS HfhQ GdHUQ aMOK ef HjfgG fhQ eHSW aCUGH GdLSO s
(3Vef eLehY , JQJjHgG (B: (3GdJGSYs
(3jdi Pdc fbhd eNJdaI ai GdMLQ GdecQ hGdUfYI GdEdgjI ef CbhGd HYV GdMceGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B204 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdaGJM (B(5309) s
Keywords: (3GdcjejGA h GdWHjYjGJs